A gestão da indisciplina pelo psicólogo escolar: bestudo do Instituto Federal de Educação, Ciência e Tecnologia da Paraíba - Rodrigues, Icaro Arcênio de Alencar (2017)
The existence of human groupings that characterize society makes it necessary to use rules of coexistence so that the individual and the group can survive. It is observed that for the human survival it is necessary the presence of work, just as it is by work that the conditions of existence of humanity are created, so it is by the education that the criteria of organization and formation for work are established. The school institutions, in order to comply with the teaching-learning goal, organize their didactic and coexistence norms, but these rules are not always fulfilled by the school community, and the students are often seen as the only one responsible for indiscipline. In this context, the Federal Network of Vocational, Scientific and Technological Education is presented, more specifically the Federal Institute of Education, Science and Technology of Paraíba, a teaching, research and extension institution that seeks to integrate technical formation with human formation in order to educate citizens aware of the productive process, scientific contributions and social relations that permeate human life. In the same way as with other educational institutions, the Federal Institutes are an area where indiscipline occurs. Belonging to the group of technicians who make the Student Assistance of the Federal Institutes, the School Psychologist is presented as a professional who needs to act collectively with the subjects and with the educational actors. To do so, this research, characterized as exploratory, field, documentary and cross – sectional research, with a qualitative and quantitative focus, investigated 13 educational psychologists of the Federal Institute of Paraíba, through a questionnaire, on how these professionals manage School indiscipline, which are the most frequent undisciplined manifestations and which strategies have been implemented by these education professionals. Based on the content analysis, it was identified that the main manifestations of indiscipline are related to the behavior of the students (65.52%), regarding interpersonal relationships, the interference of these behaviors in the classroom dynamics and in the process of teaching-learning, noncompliance of norms, non-completion of the course, situations of vulnerability in health family relations, noting that indiscipline significantly interferes in academic student life. The vast majority of psychologists work in the management of (in)discipline (92.31%) and act on various focus of attention, such as students, servants, relatives, through investigations and penalties, in the relation between teacher and student, In partnership with the management team and in meetings with a multidisciplinary team. The largest number of participants also stated that they usually exchange experiences on the management of (in)discipline (84.26%), mainly with indefinite frequency, and the pedagogical and student assistance team as a reference for this sharing. This research reaffirms the importance of the management of (in) discipline as a contribution to human formation and as a fundamental attribution in the work of the school psychologist. We present the possibility of investigating the interference of the management of (in)discipline in the students' academic performance, as the psychologists of other states manage the (in) discipline and share this management experience.